How Wages and Employment Adjust to Trade Liberalization: Quasi-Experimental Evidence from Austria - Marius Brülhart; Céline Carrère; Frederico Trionfetti (Johannes Kepler University Linz, NRN - The Austrian Center for Labor Economics and the Analysis of the Welfare State, 2012)
We study the response of regional employment and nominal wages to trade liberalization, exploiting the natural experiment provided by the opening of Central and Eastern European markets after the fall of the Iron Curtain in 1990. Using data for Austrian municipalities, we examine differential pre- and post-1990 wage and employment growth rates between regions bordering the formerly communist economies and interior regions. If the border regions are defined narrowly, within a band of less than 50 kilometers, we can identify statistically significant liberalization effects on both employment and wages. While wages responded earlier than employment, the employment effect over the entire adjustment period is estimated to be around three times as large as the wage effect. The implied slope of the regional labor supply curve can be replicated in an economic geography model that features obstacles to labor migration due to immobile housing and to heterogeneous locational preferences.
Keywords: F15; R11; R12; 330; trade liberalization; spatial adjustment; regional labor supply; natural experiment